2015
DOI: 10.1016/j.homp.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Observations on entanglement, non-locality and ultra-high dilutions

Abstract: The study and the knowledge gained from more recent theoretical models in UHD and entanglement suggest that there may be some benefit in stocktaking of what we really know about the fundamental workings of UHD as well as identifying or developing models that include measurable predictors that go beyond metaphorical descriptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…16 The issue since then evolved in an extended discussion on the so called 'entanglement theory'. 40e43 This theory or rather hypothesis may at present tend to overstretch its basis in physics, 44 but it may also open a new horizon for further research. In short, this piece of the puzzle was contrasted 2 to the above mentioned models as follows: "In recent years new explanatory hypotheses of the effect of high homeopathic dilutions have been developed, based on a theory of 'non-local' phenomenon, or 'entanglement'.…”
Section: E Homeopathy Between Physics and Psychologymentioning
confidence: 99%
“…16 The issue since then evolved in an extended discussion on the so called 'entanglement theory'. 40e43 This theory or rather hypothesis may at present tend to overstretch its basis in physics, 44 but it may also open a new horizon for further research. In short, this piece of the puzzle was contrasted 2 to the above mentioned models as follows: "In recent years new explanatory hypotheses of the effect of high homeopathic dilutions have been developed, based on a theory of 'non-local' phenomenon, or 'entanglement'.…”
Section: E Homeopathy Between Physics and Psychologymentioning
confidence: 99%
“…New developments were outlined, with special emphasis on non-local entanglement theory. 16,17 Following a classification scheme by Becker-Witt et al 18 Schulte classified studies according to publication quality 19 and concluded that the body of knowledge is promising but requires a concerted action if it is to lead to field. In an update on preliminary elements of a theory on UHDs 20 Schulte and Endler re-addressed questions surrounding different mechanisms of (i) interaction between the molecular mother substance and the solvent, (ii) storage of molecule-specific information in the solvent, (iii) physiological basis of the sensitivity of the living organism towards an UHD and (iv) interaction of the test dilution with the organism.…”
Section: Part 3 (Physics)mentioning
confidence: 99%